Scalable Fabrication of Biophotoelectrodes by Means of Automated Airbrush Spray‐Coating. Issue 7 (1st July 2020) - Bobrowski, Tim; Conzuelo, Felipe; Ruff, Adrian; Hartmann, Volker; Frank, Anna; Erichsen, Thomas; Nowaczyk, Marc M.; Schuhmann, Wolfgang
Abstract: The fabrication and electrochemical evaluation of transparent photoelectrodes consisting of Photosystem I (PSI) or Photosystem II (PSII) is described, which are embedded and electrically wired by a redox polymer. The fabrication process is performed by an automated airbrush‐type spray coating system, which ensures controlled and scalable electrode preparation. As proof of concept, electrodes with a surface area of up to 25 cm 2 were prepared. The macro‐porous structure of the indium tin oxide electrodes allows a high loading of the photoactive protein complexes leading to enhanced photocurrents, which are essential for potentially technologically relevant solar‐powered devices. In addition, we show that unpurified crude PSII extracts, which can be provided in comparatively high yields for electrode modification, are suitable for photoelectrode fabrication with comparable photocurrent densities. Abstract : Spray‐coated biophotoelectrodes : An automated spray‐coating process is used to cover transparent indium tin oxide (ITO) sheets with ITO nanoparticles followed by photocatalytically active layers of Photosystem I (PSI) or Photosystem II (PSII) embedded in an Os‐complex modified redox polymer allowing a controlled and scalable coating of electrode surfaces with up to 25 cm 2 surface area.